Rhipicephalus (boophilus) microplus “in vitro” bovine tick biocontrol with dehydrated garlic (Research, Society and Development, 2021)
The general objective of this research is to evaluate the “in vitro” efficacy of different concentrations of dehydrated garlic (Attack Plus®), for the control of Rhipicephalus (Boophilus) microplus teleogens. Dehydrated garlic (Attack Plus®) was tested “in vitro” using four groups of teleogens, in quadruplicate, containing the control group and groups containing dehydrated garlic concentrations equal to 0.1%, 0, 5% and 1%(m/v). The teleogens of the control group were immersed for 5 min in 15 mL of distilled water and 5 mL adjuvant (mineral oil), while the other concentrations were immersed for 5 min in 20 mL of a solution containing 15 mL of distilled water, 5 mL adjuvant and dehydrated garlic in their respective concentrations. After immersion, the teleogens were dried on paper towels and fixed by means of adhesive tape on Petry plates, previously identified and placed in an air-conditioned oven, regulated at a temperature of 27 ºC, relative humidity greater than 80% for 26 days to observe oviposition. Afterwards, the oviposition content was weighed in its entirety and 0.3 g of this content was stored in test tubes, sealed with cotton wool and sent back to the oven, being kept for 26 days in order to assess the percentage of hatchability. After the treatments, the performance of the product (Attack Plus®) was positively concluded through the results obtained, where all groups were effective in the results, because even if the oviposition occurred, the eggs did not hatch.